Perceived teacher support in secondary education from 1980 to 2019: An integrative review - Violeta Lozano Botellero; Stine M. Ekornes; Siv M. Gamlem; Wenche Torrissen; Helga Synnevåg Løvoll (Cogent Education, 2023)
AbstractHow teacher support is perceived in secondary school was a main purpose for examination. As teacher support is a multidimensional construct, we conducted an integrative review to identify and analyze longitudinal and cross-sectional research trends, common practices, and general results in the field of perceived teacher support in secondary education. Following the PRISMA guidelines, a total of 198 articles were analyzed by abstract/methods and 95 by full-text. Our results suggest that teacher support is strongly related to academic motivation, health, and wellbeing but several gaps in the research literature needs attention. Subject topics are rarely reported, except for science, technology, engineering, and mathematics (STEM) and physical education, which make the body of research insensitive for various learning situations and teacher competence. The research is mainly quantitative, addressing the need for more qualitative studies. The teacher perspective is also sparse. The literature has mainly focused on three types of support: social/emotional, autonomy, and academic support. The research in the area has grown steadily since 1980, with a marked increase in publications and research quality since 2009. More research using qualitative and mixed methods and focusing on teachers’ perspectives is needed in addition to more adherence to APA guidelines.